Evaluating the Fraud Triangle’s Predictive Power for Financial Statement Fraud (E-Jurnal Akuntansi, 2025)
Financial statement fraud is often perpetrated by management to conceal company losses. The underlying motivations for such fraudulent behavior are commonly explained through the fraud triangle framework, which comprises three elements: pressure, opportunity, and rationalization. This study seeks to provide empirical evidence on the influence of these fraud triangle components on the occurrence of financial statement fraud. The research sample, consisting of 90 firm-year observations from 2021 to 2023, was selected using purposive sampling. Data were analyzed using multiple linear regression to assess the impact of each component. The results indicate that external pressure does not significantly influence financial statement fraud, whereas effective monitoring exhibits a negative relationship, and rationalization shows a positive relationship with the likelihood of fraud. These findings align with the Theory of Planned Behavior and Agency Theory, both of which suggest that behavioral intentions, perceived control, and principal-agent dynamics play a critical role in shaping managerial decisions related to fraudulent financial reporting.